Effects of boron content on the microstructures and mechanical properties of reactive hot-pressed BxC-TiB2-SiC composites. Issue 16 (November 2019) - He, Qianglong; Xie, Jingjing; Wang, Aiyang; Liu, Chun; Tian, Tian; Hu, Lanxin; Yi, Chenhong; Zhang, Zhixiao; Wang, Hao; Wang, Weimin; Fu, Zhengyi
Abstract: Bx C-TiB2 -SiC ceramic composites were fabricated via reactive hot pressing using TiC, B, and Si as the raw materials. The phase transition process was studied by heating powder mixtures to different temperatures in combination with X-ray diffraction analysis. The stoichiometric ratio between B and C in boron carbide is variable. A series of powder mixtures containing excess boron (0 wt%, 10 wt%, 20 wt%, or 30 wt% B) were sintered, and the microstructures and mechanical properties of the composites were investigated. The results showed that the B6.1 C-TiB2 -SiC composite prepared from the starting powders with 30 wt% excess boron had the best comprehensive mechanical properties, with a relative density, hardness, bending strength, and fracture toughness of 98.32%, 33.2 GPa, 840 MPa, and 5.22 MPa m 1/2, respectively. Excessive boron substitution may cause lattice distortion in boron carbide, and the boron carbide grains in this state may form a large number of twins under the compressive stress generated by the TiB2 grains, which will affect the properties of the composites.